1994
DOI: 10.3177/jnsv.40.49
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eicosapentaenoic Acid Ethyl Ester on Albuminuria in Streptozotocin-Induced Diabetic Rats.

Abstract: SummaryWistar rats (4-week-old) were administered with streptozo tocin (45mg/kg) through tail veins. After 3 months, diabetic rats were divided into 2 groups. One group (EPA group, n=16) was fed a lipid-free diet (90%, w/w) plus lard (8%) and 90% pure eicosapentaenoic acid ethyl ester (2%) for 6 months. The other group (control group, n= 16) was fed in the same way except that eicosapentaenoic acid ethyl ester was replaced by safflower oil. Twenty-four-hour urine was collected just before starting the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The capacity of n-3 PUFAs to ameliorate renal damage is not restricted to our transgenic rat model. EPA was reported to retard the progression of diabetic nephropathy in streptozotocin-treated rats [42] and to prevent the development of glomerulosclerosis in a 5/6 renal ablation model [43]. Moreover, n-3 PUFAs delayed proteinuria, lowered blood pressure and improved the antioxidant status in spontaneously hypertensive rats [44,45].…”
Section: Discussionmentioning
confidence: 98%
“…The capacity of n-3 PUFAs to ameliorate renal damage is not restricted to our transgenic rat model. EPA was reported to retard the progression of diabetic nephropathy in streptozotocin-treated rats [42] and to prevent the development of glomerulosclerosis in a 5/6 renal ablation model [43]. Moreover, n-3 PUFAs delayed proteinuria, lowered blood pressure and improved the antioxidant status in spontaneously hypertensive rats [44,45].…”
Section: Discussionmentioning
confidence: 98%
“…Clinical studies have shown that treatment with n-3 PUFA lowers the risk of development of albuminuria in young type 1 diabetic patients (35) and slows the progression of albuminuria in older patients with type 2 diabetes (44). Eicosapentaenoic acid ethyl ester reduces albuminuria in STZ-induced Sprague-Dawley rats (3,19). How-…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies suggest that n-3 PUFA slow the progression of renal dysfunction, e.g., prevent the decline in creatinine clearance in healthy older people (28), lessen the risk of albuminuria in young type 1 diabetic patients (35), and slow the progression of albuminuria in older patients with type 2 diabetes (44). Furthermore, dietary PUFA have been shown to have renoprotective effects in experimental models of diabetes (3,19). However, the mechanisms by which n-3 PUFA exert this renoprotection are unclear.…”
mentioning
confidence: 99%
“…[164][165][166][167] The discrepancies could relate to differences in the fish oil preparations or the type of patients. It is also possible that some of the effects observed in short-term studies are transient, as a study from our clinic 164 using almost the same oil as in our study for 8 weeks in a cross-over study in Type 1 DM patients with micro-and macroalbuminuria did find a reduction in blood pressure and transcapillary escape rate of albumin and an improvement in the lipid profile 164 in contrast to our long-term study.…”
Section: Dietary Interventionmentioning
confidence: 99%